The Use of Participatory Rural Appraisal Technique to Identify Farmers' Needs in Agricultural Development - Perera, M.A.M.I.; Wijeratne, M. (My University, 2015)
Understanding and addressing farmers' needs are important to enhance the effectiveness of the agricultural sector of Sri Lanka where livelihoods of many depend on small scale farming. In that context, participatory rural appraisal techniques (PRA) play a key role by identifying and prioritizing the problems of farmers and guiding implementing strategies to solve them by using local knowledge. PRA is conducted with the help of outdoor facilitators using a set of participatory and visual techniques that can be easily understood by participants from rural backgrounds. This study was conducted in the Ratemulla Grama Niladhari Division in the Pahatha Hewahata Divisional Secretary’s Area of Kandy District to understand the usefulness of PRA in agricultural development. Specific objectives of this study were a) to investigate the current situation of the village, b) to identify and prioritize problems that farmers are facing, and c) to suggest solutions for the identified problems. Eighty two villagers participated actively in this exercise. Four PRA tools; resource mapping; Venn diagrams; pair wise ranking; and matrix ranking were used in the process. Findings indicate that the majority of people in the village are engaged in agriculture, and mainly in paddy cultivation. In addition they cultivate minor fruit crops, and export agriculture crops. It is revealed through Venn diagrams that relationships between government officers, institutions, organizations and the farmers are weak. Matrix ranking depicts that pepper is the most suitable crop for commercial cultivation. According to pair wise ranking, the major constraint faced by the farmers is lack of technical knowledge in farming practices. In order to solve the problems of farmers, the relevant authorized officers should frequently visit the farmers, examine the current practices and identify the prevailing weaknesses. At the same time, the relevant authorities should identify suitable crops and disseminate appropriate technical knowledge among farmers in order to enhance their livelihoods. This study thus shows that participatory rural appraisal techniques can be used to identify farmers' needs in agricultural development.
Keywords: Agricultural development; farmers' needs; participatory rural appraisal